Analysis of the Relationship between Serum Magnesium Levels and Severity of COVID-19 Patients - Muyadhil Nurindar; Ruland DN. Pakasi; Liong Boy Kurniawan (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Magnesium (Mg) plays an important role in the homeostasis functions of the lungs and heart for humankind. However, there is limited information concerning the importance of such an electrolyte mineral to COVID-19 pathogenesis. The Mg level is not primarily considered for the analysis of infectious diseases in the laboratory. The purpose of this study was to analyze the relationship between Mg levels and COVID-19 patient severity at Dr. Wahidin Sudirohusodo Hospital, Makassar. This research was a retrospective study with a cross-sectional design. Samples were prepared from 186 patients. Serum Mg levels were measured using an ABX Pentra 400C analyzer and the patients diagnosed with COVID-19 were then classified into abnormal and normal magnesemia. Based on the severity of COVID-19, patients were then categorized into severe and non-severe. The obtained data were then statistically analyzed using the Kolmogorov-Smirnov test, Mann-Whitney test, Chi-Square, and odd ratio with a significant level of p <0.05. The mean values of serum Mg levels of severe COVID-19 patients (2.53±2.03 mg/dL) were not significantly different compared to those of non-severe COVID-19 patients (2.12±0.83 mg/dL) with p=0.712. Patients with abnormal magnesemia had a 2.625 times higher risk of severe COVID-19 (95% CI = 1.499 – 4.757, p-value=0.001) compared to those with normal magnesemia. There was a significant relationship between serum Mg levels and the severity of COVID-19 patients at Dr. Wahidin Sudirohusodo Hospital. Patients with abnormal Mg levels had a 2.625 times higher risk of severe COVID-19. Magnesium concentration is an important parameter, which must be monitored in the laboratory analyses of COVID-19 patients.